Effectiveness of Cognitive-Emotional-Social Training of Working Memory on Attention Bias, Executive Functions, and Academic Performance of Students with ADHD - Sarshar , Maryam; Emadian, Seyedeh Olia; Hassanzadeh, Ramazan (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Children with Attention Deficit/Hyperactivity Disorder (ADHD) suffer from numerous complications, leading to significant psychological and social costs. Therefore, this study aimed to evaluate the effectiveness of cognitive-emotional-social training of working memory on attention bias, executive functions, and academic performance of students with ADHD. Methods and Materials: This quasi-experimental study utilized a pretest-posttest and follow-up design with a control group. A total of 32 children were purposefully selected and randomly assigned to two groups of 16 participants each. Participants were assessed before, after the intervention, and one month later using questionnaires measuring attention bias, executive functions, and academic performance. The intervention group received cognitive-emotional-social training of working memory. Data were analyzed using repeated measures analysis of variance. Findings: The results indicated a significant improvement in attention bias, executive functions, and academic performance in the intervention group compared to the control group. Conclusion: According to the obtained results, cognitive-emotional-social training of working memory is effective in improving attention bias, executive functions, and academic performance of students with ADHD.